Skin-protective biological activities of bio-fermented Aframomum angustifolium extract by a consortium of microorganisms - Albouy, Marion; Aubailly, Simon; Jeanneton, Olivier; Marteau, Clarisse; Sobilo, Lauren; Boulgana, Rachid; Bru, Gerard; Bellanger, Marine; Leblanc, Emmanuelle; Dos Santos, Morgan; Pays, Karl; Choisy, Patrick; et al. (Frontiers in Pharmacology, 2023)
Background: Aframomum sp. is a genus of plants in the Zingiberaceae family. It includes several species, some of which are used in cosmetics for their various properties, making them useful in skincare products, particularly for anti-aging, moisturizing, and brightening the skin.However, to date, there is no experimental evidence on its natural extracts obtained or modified using microorganisms (bio-fermentation) as an anti-aging agent.Objective: The present study aimed to evaluate the antiaging effect of a Bio-fermented Aframomum angustifolium (BAA) extract on 3D bioprinted skin equivalent.The consortium of microorganisms contained Komagataeibacter, Gluconobacter,